Bank-Specific Variables and Credit Risk: A Moderating Effect of Bank Type (KASBIT Business Journal, 2024)
Credit risk management has become a core activity in the banking sector, especially after the financial crisis of 2007-2008. This study aims to investigate the impact of bank-specific variables on credit risk in association with the moderating effect of bank type in Pakistan. For this purpose, the non-performing loan is taken as the dependent variable to represent credit risk. Independent variables include total equity to total assets representing capital buffer, total financing to total assets for financing expansion, interest income-interest expense to total assets as net interest margin, return on assets to represent efficiency, gross advances to deposit as a proxy of financial intermediation, log of total assets to represent bank size, crisis, and bank type. Bank type is also taken as a moderator in the second model. Annual data for 16 years (2006 to 2021) has been taken from 23 scheduled banks covering both Islamic and conventional banks for panel regression analysis. The study recommends two different models for regression analysis. First, bank type is taken as an independent variable in addition to other bank-specific variables. Later, bank type is taken as a moderator to observe if it moderates the relationship between independent variables and dependent variables. At the initial stage, taking bank type as an independent variable, a random effect model is applied followed by the Hausman test. All variables including bank type are found to be significantly related to credit risk in the model. Later, taking bank type as moderator, the random effect model is finalized to conclude the results followed by the Hausman test. Results show that bank type as moderator significantly affects the relationship of only bank size and capital buffer with credit risk. It is interpreted through results that both bank size and capital buffer of Islamic banks positively affect credit risk, and hence, an increase in these variables may lead to a higher level of credit risk as compared to conventional banks. This study will help the banking sector to improve credit risk management with respect to its type.
Keywords: Non-performing loan, bank size, credit risk, financing expansion, net interest margin.